A true tale of science and discovery - Curtis, Lawrence A. (Environmental research advances series., 2010)
Presents a view of how knowledge of the biological world increased. This book deals with science and aims at explaining one example of the scientific process, when and where it was done, who did it, what they did, why they did it that way, the circumstances under which they did it, and what the results and interpretations were.